Blakea echinata (Melastomataceae: Blakeeae): a new species from the Caribbean rainforest of Panama - Almeda, Frank; Penneys, Darin S. (Phytotaxa, 2018)
Blakea echinata from the lowland Caribbean rainforest of Panama is described, illustrated, mapped, and compared with superficially similar species. It is readily distinguished by its elongate internodes; indumentum of spreading smooth (sometimes gland-tipped) trichomes on distal branchlets, leaves, floral bracts, and calyx lobes intermixed with laterally compressed and somewhat roughened conic to clavate or ± triangular trichomes on distal branchlets, floral peduncles, and abaxial surfaces of floral bracts; rhombic reflexed basally clawed petals; yellow-orange unappendaged anthers; and ovary apex that is elaborated into a distally glandular-laciniate collar 5–6 mm long that envelops the style base. A conservation assessment of Critically Endangered is recommended for this species based on IUCN Red List Categories and Criteria.